Scaling internet routers using optics. - Keslassy, Isaac (Computer communication review.)
Routers built around a single-stage crossbar and a centralized scheduler do not scale, and (in practice) do not provide the throughput guarantees that network operators need to make efficient use of their expensive long-haul links. In this paper we consider how optics can be used to scale capacity and reduce power in a router. We start with the promising load-balanced switch architecture proposed by C-S. Chang. This approach eliminates the scheduler, is scalable, and guarantees 100% throughput for a broad class of traffic. But several problems need to be solved to make this architecture practical: (1) Packets can be mis-sequenced, (2) Pathological periodic traffic patterns can make throughput arbitrarily small, (3) The architecture requires a rapidly configuring switch fabric, and (4) It does not work when linecards are missing or have failed. In this paper we solve each problem in turn, and describe new architectures that include our solutions. We motivate our work by designing a 100Tb/s packet-switched router arranged as 640 linecards, each operating at 160Gb/s. We describe two different implementations based on technology available within the next three years.